Detrimental Effects of Saccharum officinarum Juice on Reproductive Functions of Female Wistar Rats (Nigerian Journal of Physiological Sciences, 2023)
Changing dietary compositions have contributed to the growing epidemic of metabolic diseases with serious impacts on several aspects of health, including reproductive health.  Saccharum officinarum juice has a natural sweetness that makes the general populace relinquish its use as a sweet course and well-known raw material for the production of refined sugar. Studies have reported adverse effects of this juice on male reproductive functions, but there is a paucity of information on females. This study investigated the effects of fresh Saccharum officinarum juice on the reproductive functions of female Wistar rats. A sugarcane press juicer was used to extract Saccharum officinarum juice. Twenty female Wistar rats (180-200 g) grouped into four (n = 5) received 1.0 mL/kg/day distilled water (control), and 1.0, 3.2, and 10.0 mL/kg/day of fresh Saccharum officinarum juice once daily for 21 days by gavage. Serum follicle-stimulating hormone, luteinizing hormone, and estrogen levels were measured using enzyme-linked immunosorbent assay (ELIZA). The estrous cycle was assessed using the Marcondes principle and histology of the ovary and uterus were assessed by microscopy. Data were analyzed using the Analysis of variance at a significance of p < 0.05. Saccharum officinarum juice caused an increase in the body weight and serum levels of follicle-stimulating hormone and luteinizing hormone. It altered the estrous cycle by increasing the frequency of occurrence of the proestrus phase but reduced that of the metestrus phase. The juice altered the cytoarchitecture of the ovaries via vacuolations and cysts within the ovarian stroma, while the uterine section showed distorted endometrial lining and glands. Saccharum officinarum juice inflamed the ovaries and distorted the estrous cycle and uterine endometrial lining. Saccharum officinarum juice consumption may possess deleterious effects on the reproductive functions of female Wistar rats. Keywords: Saccharum officinarum juice, Ovary, Uterus, Estrous cycle, Infertility.